Atypical presentation of TRPV3 variant: Cerebral palsy and intellectual disability without dermatologic features of olmsted syndrome - Khoodoruth, Mohamed Adil Shah (2025)
To the Editor: Olmsted syndrome (OS) is a rare genodermatosis, with limited cases reported globally, primarily characterized by progressive palmoplantar keratoderma and keratotic plaques, and is linked to mutations in the TRPV3 gene on chromosome 17p13.2.1,2 We read with great interest the case report by Frantz et al, which describes a mild presentation of OS due to a loss-of-function mutation in the TRPV3 gene (transient receptor potential vanilloid-3).3 Their patient exhibited dermatologic features, including nonpruritic hyperkeratotic palms and soles with scarring alopecia. Here, we report a 17-year-old male of Asian descent, with cerebral palsy and intellectual disability, but without any dermatologic features typically associated with OS, despite carrying a TRPV3 variant (Fig 1). He was referred for psychiatric evaluation due to academic decline, impulsivity, and emotional dysregulation. A physical exam demonstrated no evidence of palmoplantar keratoderma, periorificial plaques, or any other skin lesions. Cognitive testing revealed an FSIQ of 69 (95% confidence interval, 65-76), indicating intellectual disability. Genome-wide oligonucleotide array-based comparative genomic hybridization analysis, performed using the Human Genome CGH Microarray kit, identified an intragenic deletion of approximately 13 kilobases (kb) in the TRPV3 gene at cytogenetic band 17p13.2. The deleted genomic segment included exons 3-8 of the TRPV3 gene (arr[GRCh38] 17p13.2(3532389_3545489)×1). Since parental genetic data were unavailable, it remains unclear whether this variant was inherited or de novo.